2019
DOI: 10.1007/s40261-019-00760-1
|View full text |Cite
|
Sign up to set email alerts
|

Admissions and Cost of Hospitalisation of Phenylketonuria: Spanish Claims Database Analysis

Abstract: Background: Phenylketonuria (PKU) is a well-known rare disease which is included in the neonatal screening of many countries. Therefore there are few published data on the admissions and cost in Spain.Objective: To assess the number of admissions and economic burden of PKU in Spain.Methods: PKU patients were identified from a Spanish database containing data from public and private healthcare centres from 1997 to 2015. The parameters obtained were: characteristics of the patients, type of admissions, readmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The analysis revealed few differences to previous evaluations in the whole country. Patients' age at first admission, 14.90 years, was relatively elevated in comparison with the 4.5 years determined in Spain [11]. However, patients' diagnoses are registered in the database solely after 2007, and diagnoses made before that year are not included.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The analysis revealed few differences to previous evaluations in the whole country. Patients' age at first admission, 14.90 years, was relatively elevated in comparison with the 4.5 years determined in Spain [11]. However, patients' diagnoses are registered in the database solely after 2007, and diagnoses made before that year are not included.…”
Section: Discussionmentioning
confidence: 92%
“…This cost is presumed higher than in the general population as a consequence of the major use of healthcare resources that derives from the higher portion of patients with chronic comorbid conditions. In Spain cost estimations situated annual costs of PKU at around €4,239 in 2015, however, therein, calculation methods were based on patients' diagnoses and are not entirely comparable [11]. Currently, the majority of costs associated with the disease are indirect costs, covered by families and patients, due to the extended use of a dietary treatment [23,24]…”
Section: In Terms Of Secondary Diagnoses and Comorbidities No Clear mentioning
confidence: 99%
See 1 more Smart Citation
“…Economic factors also play an important role in the management and care of children with PKU [ 18 , 27 , 28 ]. There are two main reasons for this.…”
Section: Introductionmentioning
confidence: 99%
“…For a rare disease with effective treatments, there is especially a strong health interest relating to their economic burden. Recent studies have reported economic burden of diseases such as hemophilia [35], cystic fibrosis [6, 7], phenylketonuria [8], and fragile X syndrome [9, 10] from the perspective of patients, families, and societies in Europe, United States, and Canada.…”
Section: Introductionmentioning
confidence: 99%